Distribusi Pendapatan dan Kekayaan dalam Ekonomi Islam - Kalsum, Ummi (Li Falah: Journal of Islamic Economics and Business, 2018)
This article presents the critical study about distribution of income and wealth in Islamic economics perspective and 1945 constitution. The method of this study used descriptiveanalytical with library research approach. The result of this study showed that distribution of income and wealth is urgent in create the Human Falah. The main principles in distribution are justice and affection (brotherhood), meanwhile only there are two system of distribution, those are commercial with market mechanism and sistem which emphasize dimensions of justice for the weak people. In specifically doctrine of nationalism economy and doctrine of populist economy are present in article 33, 34, and 27, 1945 constitution of Indonesia. These articles are be the stronghold of nationalism economy and the stronghold for the prioritization of life neccesities whole of Indonesian people.